2012
DOI: 10.1111/j.1937-5956.2012.01332.x
|View full text |Cite
|
Sign up to set email alerts
|

Competition and Coordination in Online Marketplaces

Abstract: O nline marketplaces, such as those operated by Amazon, have seen rapid growth in recent years. These marketplaces serve as an intermediary, matching buyers with sellers, whereas control of the good is left to the seller. In some cases, e.g., the Amazon marketplace system, the firm that owns and manages the marketplace system will also sell competing products through the marketplace system. This creates a new form of channel conflict, which is a focus of this article. We consider a setting in which a marketpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
108
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(124 citation statements)
references
References 38 publications
1
108
0
Order By: Relevance
“…, Ryan et al. , Tsay and Agrawal ). From the perspective of the retailer, researchers have studied whether a brick‐and‐mortar retailer should adopt a dual‐channel strategy (e.g., Bernstein et al.…”
Section: Introductionmentioning
confidence: 99%
“…, Ryan et al. , Tsay and Agrawal ). From the perspective of the retailer, researchers have studied whether a brick‐and‐mortar retailer should adopt a dual‐channel strategy (e.g., Bernstein et al.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the strategic choice of platform retailing mode, Hagiu [35] provided the first comparison between two polar strategies (reselling and agent selling) for market intermediation by analyzing the indirect network effects between buyers and sellers, asymmetric information between the seller and the intermediary and investment incentives and product complementarities/substitutability. Ryan [36] provided the conditions under which a retailer that currently sells its product through its website should expand its market to the marketplace. They analyzed the optimal decisions for both the retailers and marketplace firms and characterized the system's equilibrium.…”
Section: Marketplace and Platformmentioning
confidence: 99%
“…Customers are strategic and their purchase choices are based on utility maximization [36]. We assume that customers have different product valuations, v, where v is uniformly distributed in the interval, [0,1].…”
Section: Problem Descriptionmentioning
confidence: 99%
“…At the same time, some researchers have considered the rationality of the supplier or traditional retailer selling by using online platforms. For example, Ryan et al [38] considered a setting with a supplier who sells goods through its own direct sale website and has the option of selling its goods through an online platform. In a competitive supplier environment, Tian et al [39] found that the order-fulfilment costs and upstream competition intensity are important factors affecting the online channel selection of suppliers.…”
Section: Literature Reviewmentioning
confidence: 99%